Dukawalla: Voice Interfaces for Small Businesses in Africa - Ankrah, Elizabeth; Nyairo, Stephanie; Muchai, Mercy; Awori, Kagonya; Ochieng, Millicent; Kariuki, Mark; O'Neill, Jacki (ArXiv, 2024)
Small and medium-sized businesses (SMBs) often struggle with data-driven decision-making due to a lack of advanced analytics tools, especially in African countries where they make up majority of the workforce. Though many tools exist they are not designed to fit into the ways of working of SMB workers who are mobile-first, have limited time to learn new workflows, and for whom social and business are tightly coupled. To address this, the Dukawalla prototype was created. This intelligent assistant bridges the gap between raw business data and actionable insights by leveraging voice interaction and the power of generative AI. Dukawalla provides an intuitive way for business owners to interact with their data, aiding in informed decision-making. This paper examines Dukawalla’s deployment across SMBs in Nairobi, focusing on their experiences using this voice-based assistant to streamline data collection and provide business insights.